Средневековые миры Центрально-Восточной Европы в сравнительной перспективе: Польша пястов и Русь рюриковичей - Мусин, А. (Княжа доба: історія і культура, 2019)
Рассматриваются вопросы методологии и эпистемологии компаративистских исследований средневековой Центрально-Восточной Европы. Дается критический анализ предшествующей историографии, демонстрируется ее зависимость от политической ситуации. Отмечается, что сравнительные исследования должны избавиться от тирании ретроспекции, которая переносит стереотипы новейшего времени не раннее средневековье. В исследовании сравнение не является целью, а выполняет роль методологии, позволяющей выявить особенности конкретного общества и политии. Важная роль принадлежит анализу материальных и пространственных объектов, упомянутых в средневековых текстах. Центр исследований переносится с изучения идентичности на иерархию ценностей. Восточно-европейская сравнительная перспектива позволяет описать польскую культуру в контексте византийских и древнерусских ценностей и vice versa, подчеркнув особенности Центрально-Восточной Европы как “большой границы” между восточно-христианской и латинской цивилизациями. Системно анализируется ряд взаимосвязанных эпизодов Повести временных лет и Киевского свода. Выводы свидетельствуют об отсутствии негативного отношения к ляхам, Лядская земля занимает в ценностной иерархии место, сравнимое с Руськой землей, а изображение беса в образе ляха является топосом агиографии и получает антипольскую интерпретацию только в Новое время. Дается анализ двух эпизодов Cronicae et gesta ducum sive principum Polonorum. Жест князя Болеслава Храброго, ударившего мечом Золотые Ворота в Киеве (I: 7) рассматривается на широком сравнительном фоне IX–XIV вв. (Повесть временных лет, Киевский свод, Theophanes Chronographia, Symeonis Metaphrastis Chronographia, Gesta Hungarorum, Miracula Sancti Johannis Eboracensis Episcopi, Annales Fuldenses, скандинавские саги, белорусско-литовские летописи, сочинения Мацея Сирийковского). В результате поступок Болеслава оценивается как реализация библейского образа из пророчества Иезекеиля (Иез. 25: 15). Эпизод с бородой руського князя (I: 23) интерпретируется как ритуал клятвы, оставшийся непонятным латинскому хронисту. Поход Болеслава Храброго на Киев 1018 г. в контексте информации Chronicon Thietmari Merseburgensis (VIII: 33) оценивается как намерение Пястов найти свое место в трансконтинентальной торговле с Византией. В целом Польша и Русь предстают как политии с архаичными социально-экономическими отношениями, однако в Польше можно наблюдать передовое развитие культуры, связанное с иным типом христианизации. The article starts with the methodology and epistemology of comparative studies of medieval East-Central Europe. The critical analysis of the previous historiography is done, and its dependency on the political situation and ideology is shown. The author stresses that the comparative studies must be free of the tyranny of retrospection which brings the modern stereotype into medieval past. The comparison is not regarded as a goal of research, and plays the role of a methodological approach. It should allow detecting and analyzing special features of local societies and polities. The important role is attributed to the study of material and spatial objects, mentioned in medieval texts. The main scop of researches shifts from the study of identities to the analysis of hierarchy of historical values. East-European comparative perspective lets to describe the medieval Polish society and culture in the term of Byzantine and Rus’ values orientation and vice versa, that should stress the features of East-Central Europe as “big frontier” between East-Christian and Latin civilizations. The author analyses systematically a series of interlaced episodes of the Rus’ Primary Chronicle and Chronicle of Kiev. The conclusions show the absence of any negative stereotypes towards the Poles (Lyaches), the Polish Land possessed a high rank position in the Rus’ hierarchy of values, comparable to the Rus’ Land, and the representation of a demon as a Pole in the Chronicle was only a topos of hagiography; it had had anti-Polish interpretation only in Modern Times. The article also propose the contextual study of two episodes from Cronicae et gesta ducum sive principum Polonorum. The gesture of Boleslave the Brave hitting the Golden Gates of Kiev with his sword (I: 7) is studied at the large comparative background of the 9th-14th centuries (Rus’ Primary Chronicle, Chronicle of Kiev, Theophanes Chronographia, Symeonis Metaphrastis Chronographia, Gesta Hungarorum, Miracula Sancti Johannis Eboracensis Episcopi, Annales Fuldenses, Scandinavian Sagas, Chronicles of Lithuania and Bielarus, Maciej Stryjkowski). It is interpreted as a biblical motive, more precisely as fulfillment of prophecy of Ezekiel (25: 15). The episode with the beard of a Rus’ prince (I: 23) is interpreted as a rital of sermon which was strange for the Latin chroniсler who did not understand its meaning. The raid of Boleslave the Brave to Kiev in 1018 within the information of the Chronicon Thietmari Merseburgensis (VIII: 33) is evaluated as an ambition of the Piast dynasty to obtain its place in the transcontinental trade to Byzantium. In general early medieval Poland and Rus’ present themselves as polities with archaic social and economic system; however, in Poland different level of cultural development within the progress of Christianization can be observed.